2019
DOI: 10.1042/bsr20182480
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of SOX18 inhibits laryngeal carcinoma cell proliferation, migration, and invasion through JAK2/STAT3 signaling

Abstract: Laryngeal carcinoma is one of the most common malignant tumors of the head, neck, and respiratory tract. The aim of the present study is to explore the biological function of SRY-related HMG-box 18 (SOX18) in laryngeal carcinoma cells and study the molecular mechanism involved. Initial findings indicate that the expression of SOX18 was increased in laryngeal carcinoma cell lines and tissues. The effect of SOX18 on laryngeal carcinoma cell proliferation, cell cycle, apoptosis, invasion, and migration was also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The JAK2/STAT3 pathway is participated in the progression of lymphangiogenesis, and SOX18 has been reported to regulate this pathway [ 25 ]. Therefore, we investigated whether SOX18-mediated JAK2/STAT3 activation was involved in lymphangiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JAK2/STAT3 pathway is participated in the progression of lymphangiogenesis, and SOX18 has been reported to regulate this pathway [ 25 ]. Therefore, we investigated whether SOX18-mediated JAK2/STAT3 activation was involved in lymphangiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 has been also showed to promote lymphangiogenesis via activation of the JAK/STAT3 signaling [ 39 , 40 ]. SOX18 has been showed to regulate the JAK2/STAT3 pathway to promote laryngeal carcinoma cell growth, cell motility, and invasion [ 25 ]. Consistently, we found that the ectopic experssion of SOX18 increased the phosphorylation of JAK2 and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with Ma et al ., 15 who concluded that high expression of SOX18 might be a predictive marker of bad prognostic types of esophageal SCC. Furthermore, Xu et al ., 16 demonstrated that SOX18 was overexpressed in laryngeal SCC, and its expression correlated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Francois et al ., 6 reported that SOX18 is essential for stimulation of the prospero homeobox 1 promoter that is required for the development of new blood and lymphatic vessels in tumor evolution and metastasis. Furthermore, Xu et al ., 16 concluded that SOX18 regulated the cell proliferation, cell cycle, apoptosis, migration, and invasion of tumor cells via JAK2/STAT3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of ROS produced during apoptosis is derived from mitochondria, and the increase in ROS is directly related to apoptosis (18). Moreover, according to a study of Xu et al (19), lowering the phosphorylation level of STAT3 can effectively reduce the mitochondrial membrane potential, increase the content of ROS in cells, and induce mitochondrial apoptosis. In the present study, the results revealed that downregulation of miR-19a expression in osteosarcoma cells markedly increased the content of ROS in cells, suppressed the JAK2/STAT3 signaling pathway in cells, and markedly reduced the expression levels of p-JAK2, p-STAT3 and anti-apoptotic protein Mcl-1.…”
Section: Discussionmentioning
confidence: 99%